Molecular mechanisms of genetic variation and transcriptional regulation of CYP2C19 - Helsby, Nuala A.; Burns, Kathryn E. (Frontiers in Genetics, 2012)
Inherited variation in the function of the drug metabolising enzyme CYP2C19 was first observed 40 years ago. The SNP variants which underpin loss of CYP2C19 function have been elucidated and extensively studied in healthy populations. However, there has been relatively meagre translation of this information into the clinic. The presence of genotype-phenotype discordance in certain patients suggests that changes in the regulation of this gene, as well as loss of function SNPs, could play a role in deficient activity of this enzyme. Knowledge of the molecular mechanisms which control transcription of this gene, reviewed in this article, may aid the challenge of delivering CYP2C19 pharmacogenetics into clinical use.